2016
DOI: 10.3390/en9090722
|View full text |Cite
|
Sign up to set email alerts
|

Design and Optimization of Thermophotovoltaic System Cavity with Mirrors

Abstract: Thermophotovoltaic (TPV) systems can convert radiant energy into electrical power. Here we explore the design of the TPV system cavity, which houses the emitter and the photovoltaic (PV) cells. Mirrors are utilized in the cavity to modify the spatial and spectral distribution within. After discussing the basic concentric tubular design, two novel cavity configurations are put forward and parametrically studied. The investigated variables include the shape, number, and placement of the mirrors. The optimization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Both Auger and SRH recombination will increase the dark current and limit the device performance [161]. Recently, Zhou et al [162] investigated the utilization and optimization of TPV system cavity, which consists of emitter, PV cells, and mirrors to modify the spatial and spectral distribution within the system. It was demonstrated that careful design of the cavity configuration can significantly enhance the performance of the TPV cell.…”
Section: Performance Of Ingaas-based Tpv Cellmentioning
confidence: 99%
“…Both Auger and SRH recombination will increase the dark current and limit the device performance [161]. Recently, Zhou et al [162] investigated the utilization and optimization of TPV system cavity, which consists of emitter, PV cells, and mirrors to modify the spatial and spectral distribution within the system. It was demonstrated that careful design of the cavity configuration can significantly enhance the performance of the TPV cell.…”
Section: Performance Of Ingaas-based Tpv Cellmentioning
confidence: 99%
“…To date, most research on TPV/STPV systems has focused on PV cells [18]- [25], absorbers/emitters [26]- [34], and optical filters to reflect out-of-band photons back to the emitter [31]- [36]. However, the design of optical cavities for STPV systems has rarely been studied, despite the fact that optical cavities can be used to increase the system efficiency, photon recycling (also known as photon recuperation or regenerative TPV [35]), and emitter-to-cell effective view factor [37], [38]. Optical cavities can be made using durable and relatively inexpensive mirror-polished metallic surfaces that direct the radiation from the emitter toward the TPV cell [39].…”
Section: Ellipsoidal Optical Cavities For Enhanced Thermophotovoltaicsmentioning
confidence: 99%
“…To date, most research on TPV/STPV systems has focused on PV cells [18]- [25], absorbers/emitters [26]- [34], and optical filters to reflect out-of-band photons back to the emitter [31]- [36]. However, the design of optical cavities for STPV systems has rarely been studied, despite the fact that optical cavities can be used to increase the system efficiency, photon recycling (also known as photon recuperation or regenerative TPV [35]), and emitter-to-cell effective view factor [37], [38]. Optical cavities can be made using durable and relatively inexpensive mirror-polished metallic surfaces that direct the radiation from the emitter toward the TPV cell [39].…”
Section: Ellipsoidal Optical Cavities For Enhanced Thermophotovoltaicsmentioning
confidence: 99%